Study of pollution by heavy elements in some parts of Baghdad - Baghdad Science Journal (مجلة بغداد للعلوم)
The objective of the present work is to measuring the concentration of heavy elements (Pb, Cd, Zn, As) in Baghdad's soil city and indication to the probable sources of pollution as well as comparing the concentration of heavy elements with local and international ranges. The Sampling and analyzing conducted in the present work included ( 15 ) Samples from Baghdad city ( three samples for each location ).The rates of heavy elements in soil samples were as following:. Pb ( 67.5 ) ppm, Cd ( 4.11 ) ppm , Zn ( 77.9 ) ppm , As ( 4.64 ) ppm. According to the results, we find increasing in the concentrations of the heavy elements ( Pb, Cd, Zn ) in soils and decreasing in ( As ).We conclude that the main reason behind the increasing of the concentrations of heavy elements in Baghdad city's soils is due to the anthropogenic activities like the domestic wastes, the products released from the combustion of fuel containing ( tetraethyl lead ), and the industrial wastes (solid , liquid and gaseous) especially from oil industries. Other important factor that added to the pollution with these heavy elements is the three successive wars that Iraq had subjected. The explosion of rockets and bombs contributed mainly to the pollution of soil.